2005
DOI: 10.1007/s00125-005-1759-6
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and risk of type 1 diabetes in children and young adults: a population-based register study

Abstract: Aims/hypothesis: We investigated the association between type 1 diabetes and birthweight by age at disease onset. Methods: This population-based case-referent study used data from two nationwide case registers that are linked to the Swedish Medical Birth Registry and cover incident cases of type 1 diabetes in the 0-to 14-year (since 1 July 1977) and 15-to 34-year age groups (since 1 January 1983). Of the cases linked to the Medical Birth Registry, a total of 9,283 cases with onset before 15 years of age was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 11 publications
1
31
2
3
Order By: Relevance
“…MPH = SDS birth length or height−SDS MPH Diff., difference from study, care was taken to obtain the birth length and birthweight data from the growth curves maintained for each child by the Child Health Services. Several epidemiological studies have reported that type 1 diabetic children have a higher birthweight [10][11][12][13]. This was not observed in the present group of children developing diabetes before 6 years of age.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…MPH = SDS birth length or height−SDS MPH Diff., difference from study, care was taken to obtain the birth length and birthweight data from the growth curves maintained for each child by the Child Health Services. Several epidemiological studies have reported that type 1 diabetic children have a higher birthweight [10][11][12][13]. This was not observed in the present group of children developing diabetes before 6 years of age.…”
Section: Discussioncontrasting
confidence: 69%
“…High birthweight has been reported as a risk factor for type 1 diabetes [10][11][12][13]. We have demonstrated that children born with type 1 diabetes high-risk HLA genotypes had an increased risk of high birthweight corrected for gestational age (i.e.…”
Section: Introductionmentioning
confidence: 84%
“…However, the observed association between childhood-onset type 1 diabetes and birthweight may not hold for adult-onset type 1 diabetes, as two large studies [58,59] investigating type 1 diabetes diagnosed in young adults have shown little evidence of association with birthweight.…”
Section: Discussionmentioning
confidence: 99%
“…Several HLA-DQ and -DR alleles and genotypes are associated with risk and protection to different degrees [3], and the INS variable number of tandem repeats (VNTR) class I or its surrogate marker, the -23HphI A allele, has consistently been found to confer increased risk of type 1 diabetes [4,5]. Accumulating evidence suggests that environmental factors may play a role early in life [6] and that there is an effect of size at birth and other perinatal factors on the risk of type 1 diabetes, generally of relatively small magnitude [7][8][9][10][11]. Several large-scale studies have found a high birthweight to be associated with a modest but statistically significant increase in the risk of childhood-onset type 1 diabetes [8,9,11], although other, predominately smaller studies have not found a significant association [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that environmental factors may play a role early in life [6] and that there is an effect of size at birth and other perinatal factors on the risk of type 1 diabetes, generally of relatively small magnitude [7][8][9][10][11]. Several large-scale studies have found a high birthweight to be associated with a modest but statistically significant increase in the risk of childhood-onset type 1 diabetes [8,9,11], although other, predominately smaller studies have not found a significant association [e.g. 7,12].…”
Section: Introductionmentioning
confidence: 99%